The Role of Structure Canopy of Terminalia Catappa Linn. on Light Penetration and Decreasing Ambient Temperature as Climate Change Mitigation - Marjenah Marjenah (Wood Research Journal, 2021)
Terminalia catappa  (Tropical almond) is a tree that usually grows on the seashore. this tree has a shady canopy. This tree is usually planted as an ornamental plant or a shade plant on the side of the road. The presence of the Terminalia catappa tree can provide coolness if the tree is planted in the garden or in the yard or along the roadside. This research was carried out in areas around East Kalimantan, at the sampling location (Balikpapan City, Samarinda City, Tenggarong Ciyt), 25 trees Tropical almond  were set in each city which were used as the test samples trees. Data taken includes a) data on physical environmental characteristics including light intensity, ambient temperature and humidity under the canopy performed and out of canopy on each tree sample, and b) data on morphological characteristics (location, height, diameter at breast height, and shape / width of crown ). The relationship between the volume, light penetration and decreased ambient of the tropical almond tree canopy on light penetration under and in the out area of the canopy of the tropical almond tree indicated that there was an effect of the volume of the tropical almond tree canopy on light penetration and there was an effect of light penetration of the tropical almond canopy on a decrease in ambient temperature. The relationship between light penetration and increase of relative humidity indicated that there was an effect of light penetration of the tropical almond canopy on a increase in relative humidity.